2020
DOI: 10.1186/s13287-020-01935-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect and safety of stem cell therapy for chronic liver disease: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Stem cell therapy is becoming an emerging therapeutic option for chronic liver disease (CLD). However, whether stem cell therapy is more effective than conventional treatment remains questionable. We performed a large-scale meta-analysis of randomized controlled trials (RCTs) to evaluate the therapeutic effects and safety of stem cell therapy for CLD. Methods We systematically searched MEDLINE, EMBASE, the Cochrane Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
0
27
1
Order By: Relevance
“…Stem cell transplantation is an alternative option for liver transplantation in HBV-related end-stage liver disease patients [ 19 ]. A large-scale meta-analysis of randomized controlled trials (RCTs) evaluating the therapeutic effects and safety of stem cell therapy for chronic liver disease (CLD) revealed that stem cell therapy is a safe and effective therapeutic option for CLD and that patients with ACLF benefit the most in terms of improved short-term survival rates [ 20 ]. The results of our previous research showed that UCMSCs also have good therapeutic effects for HBV-related ACLF and liver cirrhosis and that their therapeutic effect could be enhanced by prolonging the UCMSC treatment course [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell transplantation is an alternative option for liver transplantation in HBV-related end-stage liver disease patients [ 19 ]. A large-scale meta-analysis of randomized controlled trials (RCTs) evaluating the therapeutic effects and safety of stem cell therapy for chronic liver disease (CLD) revealed that stem cell therapy is a safe and effective therapeutic option for CLD and that patients with ACLF benefit the most in terms of improved short-term survival rates [ 20 ]. The results of our previous research showed that UCMSCs also have good therapeutic effects for HBV-related ACLF and liver cirrhosis and that their therapeutic effect could be enhanced by prolonging the UCMSC treatment course [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale meta-analysis of randomized controlled trials (RCTs) evaluating the therapeutic effects and safety of stem cell therapy for chronic liver disease (CLD) revealed that stem cell therapy is a safe and effective therapeutic option for CLD and that patients with ACLF bene t the most in terms of improved short-term survival rates (20). The results of our previous research showed that UCMSCs also have good therapeutic effects for HBV-related ACLF and liver cirrhosis and that their therapeutic effect could be enhanced by prolonging the UCMSC treatment course (10).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the spectrum of etiologies related to these conditions is broad, including viral infections, autoimmune diseases, alcohol abuse and metabolic diseases. Likewise, marked heterogeneity is observed among studies regarding injection dose, cell source, delivery route and study design [ 50 , 51 , 52 ]. Therefore, the conjunction of multiple experimental protocols and the diversity in the etiology of liver diseases may lead to varying results in MSC therapy and derive in selection bias.…”
Section: Mesenchymal Stem Cells and Liver Regenerationmentioning
confidence: 99%